PENGARUH FAKTOR-FAKTOR SKEPTISISME PROFESIONAL AUDITOR TERHADAP PEMBERIAN OPINI (Studi Empiris Pada Pemeriksa BPK RI Provinsi Jawa Tengah) - Astari Bunga Pratiwi; Indira Januarti (Diponegoro Journal of Accounting, 2013)
The purpose of this reserach is to determine the influence of these factors on professionalskepticism towards giving opinions. These factors are ethics, experience, and expertise.The sample of this research are auditors who worked on Badan Pemeriksa Keuangan (BPK)Representative of Central Java Province. The sample was conducted by purposive samplingmethod. Collecting data was conducted by questionnare distributed directly to auditors as much 70and only 41 questionnare replayed. The data collected were processed using Partial Least Square(PLS).The result of this research showed that the ethics, experience, and expertise had nosignificant effect giving opinions with professional skepticism of auditors. Ethics and expertise hasa significant effect on giving opinions. While the experience has no significant effect on givingopinions.